Investment Commitments Remain Stable in Latin America While the Number of New Projects Declines - Izaguirre, Ada Karina (World Bank, Washington, DC, 2012)
Private activity in infrastructure in Latin America and the Caribbean showed mixed results in 2008, according to just-released data from the Private Participation in Infrastructure Project database. Investment in new projects slowed in the second half of the year with the full onset of the financial crisis. This slowdown led to a decline in the number of projects for the entire year. The region accounted for 26 percent of the year's total investment commitments in developing countries, the second largest share among developing regions. In 2008, 41 infrastructure projects with private participation reached financial or contractual closure in eight low- or middle-income countries in the region. These projects involve investment commitments (hereafter, investment) of US$14.6 billion. Infrastructure projects implemented in previous years had additional commitments of US$25.7 billion, bringing total investment in 2008 to US$40.3 billion. That represented an increase of 2 percent from the level reported in 2007. Investment in existing projects, up 12 percent from the level in 2007, drove the increase.